2012
DOI: 10.1002/chem.201103489
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Aerobic Intermolecular Cyclization of Acrylic Acid with 1‐Octene to Afford α‐Methylene‐γ‐butyrolactones: The Remarkable Effect of Continuous Water Removal from the Reaction Mixture and Analysis of the Reaction by Kinetic, ESI‐MS, and XAFS Measurements

Abstract: Further study of our aerobic intermolecular cyclization of acrylic acid with 1-octene to afford α-methylene-γ-butyrolactones, catalyzed by the Pd(OCOCF(3))(2)/Cu(OAc)(2)⋅H(2)O system, has clarified that the accumulation of water generated from oxygen during the reaction causes deactivation of the Cu cocatalyst. This prevents regeneration of the active Pd catalyst and, thus, has a harmful influence on the progress of the cyclization. As a result, both the substrate conversion and product yield are efficiently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, Stults, Friedman, and co-workers were the first to use synchrotron XAFS in a study of homogeneous catalysts using a Rh complex . Following this pioneering study, homogeneous catalysts involving Ti, V, Cr, Mo, Mn, Fe, Ru, Ni, Pd, Au, and Cu were studied by XAFS. Note that one of the authors succeeded in elucidating the mechanism of paramagnetic Fe-catalyzed Kumada–Tamao–Corriu coupling by a solution-phase XAFS analysis .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, Stults, Friedman, and co-workers were the first to use synchrotron XAFS in a study of homogeneous catalysts using a Rh complex . Following this pioneering study, homogeneous catalysts involving Ti, V, Cr, Mo, Mn, Fe, Ru, Ni, Pd, Au, and Cu were studied by XAFS. Note that one of the authors succeeded in elucidating the mechanism of paramagnetic Fe-catalyzed Kumada–Tamao–Corriu coupling by a solution-phase XAFS analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Authors founded that, starting from Cr(III) in the Cr(acac) 3 precursor, a (PNP)Cr(II)-(CH 3 ) 2 complex (PNP = bidentate diphosphinoamine) is formed upon adding bidentate diphosphinoamine and modified methylaluminoxane (MMAO), which is the active species that converts ethylene to 1-octene by passing a reversible redox cycle, while reduction to Cr(I) leads to deactivation. Miyoshi et al[831] deeply investigated the aerobic intermolecular cyclization of acrylic acid with 1-octene to afford -methylene--butyrolactones, catalysed by the Pd(OCOCF 3 ) 2 /Cu(OAc) 2 H 2 O system. They found that the accumulation of water generated from oxygen during the reaction causes deactivation of the Cu co-catalyst.…”
mentioning
confidence: 99%
“…Furthermore, Cu K-edge XANES data showed that not only Cu(II), but also Cu(I), species are present when the reaction proceeds efficiently. Authors concluded that the Cu(II) species is partially reduced to the Cu(I) species when the active Pd catalytic species are regenerated[831].…”
mentioning
confidence: 99%
“…On the basis of the above results, a plausible mechanism for the Pd-catalyzed oxidative annulations is illustrated in Scheme . We proposed that the initial step involved the coordination and ligand exchange of the acrylic derivative 2 with Pd II to provide X–Pd intermediate I . , Then, exo coordination of 1a and insertion of the diarylethyne molecule into I gave the vinyl–palladium complex II . Subsequently, the intramolecular Heck-type process afforded the alkyl-palladium species III , which would undergo β-hydride elimination to release product 3 and Pd 0 .…”
mentioning
confidence: 99%